2010
DOI: 10.1177/0269215510386254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined aerobic and resistance training on metabolic control, cardiovascular fitness and quality of life in adolescents with type 1 diabetes: a randomized controlled trial

Abstract: To evaluate the effect of combined exercise training on metabolic control, physical fitness and quality of life in adolescents with type 1 diabetes. Design: A double-blind randomized controlled trial with patients receiving combined aerobic and strength or no training. Setting: University Hospital Ghent (Belgium). Subjects: Sixteen children with type 1 diabetes were randomized into a control group (n ¼ 8) and an intervention group (n ¼ 8). Interventions: Patients participated twice a week for 20 weeks in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 25 publications
1
116
0
11
Order By: Relevance
“…In addition, the results of the present study showed a slight increase in HDL concentration after endurance (9.52%) and sprint (16.66%) exercise trainings. These slight increases may be attributable to changes of lipoprotein lipase (28) and cholesteryl ester transfer protein activity following exercise training (29). Besides, the findings are consistent with other studies (5,30), which showed a positive and significant correlation between PON1 activity and serum HDL levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the results of the present study showed a slight increase in HDL concentration after endurance (9.52%) and sprint (16.66%) exercise trainings. These slight increases may be attributable to changes of lipoprotein lipase (28) and cholesteryl ester transfer protein activity following exercise training (29). Besides, the findings are consistent with other studies (5,30), which showed a positive and significant correlation between PON1 activity and serum HDL levels.…”
Section: Discussionsupporting
confidence: 91%
“…16,17 However, only 4 studies have studied the impact of both aerobic and anaerobic training in the same patients with T1D. [18][19][20][21] Reports from these studies to date have not provided estimates of rate of change in plasma or interstitial fluid glucose in the same individual with aerobic and resistance activity under otherwise comparable dietary and insulin managements conditions.…”
Section: Impact Of Aerobic Versus Anaerobic Exercise On Plasma Glucosmentioning
confidence: 99%
“…Other studies revealed similar significant results [4][5][6]9,19,20] which showed that improvement was associated with the frequency of physical activity [4,20]. Slight decrease in HbA1c was observed with combination of aerobic and muscle strength exercise training program [10,14] and was better with competitive sport [21].…”
Section: Discussionmentioning
confidence: 63%
“…Many studies of type 1 diabetes children or adolescent have demonstrated that exercise have a beneficial effect in type 1 diabetes. It lowers blood pressure [4], improves lipid profile [5,6], endurance capacity [7], body composition of fat to muscle mass ratio [8][9][10][11], physical fitness [7], insulin sensitivity [12], bone mineral density [11], vascular function [7], antioxidant capacity [13] and overall quality of the life [10,14].…”
Section: Introductionmentioning
confidence: 99%